Analysis of the severity of foot rot disease (Phytophthora sp.) on pomelo (Citrus maxima) in Pangkep Regency, South Sulawesi - Baharuddin Patandjengi; Tutik Kuswinanti; Nurul Fauziah (Department of Plant Pest and Diseases, Faculty of Agriculture, Hasanuddin University, 2025)
Foot rot disease (FRD) on citrus plants is suspected to be caused by a Phytophthora spp., characterized by yellowish-brown stem discoloration and cracking or peeling bark. FRD spreads rapidly and can be fatal to citrus crops. The purpose of this study was to determine the intensity of FRD on pomelo (Citrus maxima) in Ma'rang, Segeri, and Labakkang Districts, Pangkep Regency. Symptomatic tissues were collected and examined microscopically at the Plant Disease Laboratory at Hasanuddin University. The highest disease intensity was observed in Ma'rang (27%), followed by Labakkang (21%) and Segeri (17%). The study also found that disease intensity was inversely related to light penetration under the canopy. Denser foliage with limited pruning resulted in lower light intensity and higher disease severity. The low intensity of light that enters under the trees canopy of pomelo plantations is affected by tree stands that have relatively denser crowns due to the infrequent pruning of less productive branches.